Classical Open-population Capture-Recapture Models.(2005). Handbook of Capture-recapture Methods. - Pollock, K.H. (2005)
In the previous chapter closed capture–recapture models were considered for situations where the population size does not change during the study. When open-population models are used, the processes of birth, death, and migration are allowed, and therefore the population size can change during the study. Studies of open populations often cover extended time periods, and the population changes that occur are of great interest to ecologists and managers. The most popular model of this open model class is the Jolly-Seber (JS) model (Jolly 1965; Seber 1965, 1982; Pollock et al. 1990; Schwarz and Seber 1999), which requires that the number of uniquely marked and unmarked animals be recorded on each trapping occasion. Therefore, a complete capture history of each captured animal is available. The model allows estimation of the parameters pertaining to population sizes, survival rates, recruitment numbers, and capture probabilities. However, it is not possible to separate survival from emigration or recruitment from immigration without additional information.